Radiostereometric migration measurement of an uncemented Cerafit® femoral stem: 26 patients followed for 10 years - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Tschunko, Franz (Biomedizinische Technik, 2017)
Radiostereometric analysis (RSA) is the gold standard for evaluating micromotions of orthopaedic implants. The method is applied for identifying novel design weaknesses in endoprostheses. Current research frequently assesses relatively short time periods. Short-term RSA studies have been widely used for predicting the long-term stability of many hip prosthetic designs, but only a few studies have focused on uncemented hip implants, especially for extended periods. The purpose of this study was to analyse the migration pattern of the Cerafit® femoral stem within 10 years and to verify the predictive value of short-term RSA after 2 years for this uncemented femoral hip stem. Twenty-six patients were followed for 10 years. Ten years after implantation, a mean subsidence of 0.22 mm±0.56 mm, a mean internal rotation of 0.59°±1.67° and a mean maximum total point motion (MTPM) of 1.28 mm±0.54 mm were detected. The main migration took place in the first 6 weeks after surgery (subsidence of 0.36 mm±0.73 mm; internal rotation of 0.62°±1.49°, MTPM of 1.05 mm±0.68 mm). All the migration values measured were small. No late-onset migration was observed. This study suggests that the Cerafit® implants are stable after 10 years. Thus, RSA could be the best tool to assess long-term implant behaviour.
EVALuna2:33711